EVALUASI TINGKAT KEMATANGAN BUAH TERHADAP MUTU TEPUNG PISANG KEPOKYANG DIHASILKAN - Harefa, Wasnidar; Pato, Usman (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
Banana flour is the result of grinding of dried banana or banana gaplek. Kepok  banana (Musa paradisiaca formatypica) is quite perspective in the development of local food sources because banana can grow in various regions in Indonesia so that fruit production is always available.  Banana fruit quickly damage after harvest. To overcome the damage, the banana was processed into flour so as to increase the economic value of kepok banana.  This research aimed to determine the quality of kepok banana flour produced with various levels of fruit maturity.   Method used in this study was Completely Ramdomized Design Experiment which consists of 4 treatments and 4 replications. Data obtained were analyzed statistically using Analysis of Variance (Anova), if Fcount ≥ Ftable then continued with Duncan's New Multiple Range Test (DNMRT) test at 5% level.  The results showed that the level of maturity of banana fruit significantly affected the moisture, ash and starch contents as well as the color and flavor of banana flour.The selected treatment was treatment P2 which produced the best quality of banana flour withmoisture content 4.74%, ash 1.59%, starch 51.05%, aroma with score 3 (slightly banana-scented ), color with a score of 3 (yellowish white) and the overall hedonic test panelis gave a score of 4 (like). Keywords: kepok banana, flour banana